Analisis Kebutuhan Pengembangan Buku Ajar Elektronika Dasar Berbantuan Simulasi Proteus Bagi Mahasiswa Pendidikan Fisika - Nadia Azizah (Kappa Journal, 2024)
The importance of basic electronics to be learned by students majoring in physics education leads to problems faced by students exploring the concept of electronics and using Proteus as a solution to connect the integration between theory and practice. Integration of textbooks in the use of Proteus is highly recommended to achieve optimal learning outcomes. However, lecturer need to design relevant and interesting materials, while increasing motivation to learn. This study aims to conduct an analysis of the needs of developing basic electronics textbooks assisted by Proteus simulations. Educational research with a descriptive type used quantitative and qualitative methods offers a comprehensive understanding. Data collection was carried out using a survey of physics education students at IAIN Palangkaraya, to then be analyzed using the Pearson correlation test. The results of the study indicate that Proteus is prepared as a tool that can improve students' practical skills and understanding of electronic principles, making learning more interactive and effective so that basic electronics e-books assisted by Proteus simulations become a necessity in lectures for physics education students